Identifikasi Timbal (PB) pada Lipstik yang Digunakan oleh Mahasiswi Angkatan 2016 Prodi d-III Analis Kesehatan UIT - syelviana A; Putri Junisya Mappa; Aprilia Zamratun Syafa’a Stori (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2020)
This study aims to find out the dangers of Lead (Pb) for health and to identify Lead (Pb) in Lipstick used by female students class of 2016 health analysts Of The University of Indonesia Timur Makassar. The type of research used is experimental research using lipstick samples as many as 5 samples with different brands. The examination was conducted using a solution of Potassium Iodide tester 0.5 N. Based on the results of studies that have been conducted on lipstick samples, all of them are positive to contain Lead (Pb) and obtained a percentage of 100% of the number of positive samples (+) and 0% of the number of negative samples (-). It is expected to consumers to be more careful in choosing lipstick to be used. Keywords: , ,